Bacteriological Profile and Antimicrobial Susceptibility of Congenital Nasolacrimal Duct Obstruction-Associated Conjunctivitis - Khan, Umair Naeem; Shahid, Muhammad; Sarwar Khan, Muhammad Imran; Fatima, Samar; Afsar Khan, Junaid; Akbar, Bushra (Pakistan Armed Forces Medical Journal, 2026)
Objective: To find out the common causes of bacterial conjunctivitis in infants having congenital nasolacrimal duct obstruction and to find out suitable and effective topical antibiotics for their infection.Study Design: Cross Sectional study.Place and Duration of Study: Department of Ophthalmology, Combined Military Hospital, Lahore Pakistan, from Jul 2024 to Dec 2024.Methodology: Infants up to the age of 01 years presenting to our department with pus and watery discharge form one or both eyes were included in current study who had previously not used any antibiotics, or left topical antibiotics for the past 2 weeks a least were included. Presence of nasolacrimal dust obstruction was confirmed with dye disappearance test. Infants with an abnormal dye disappearance test were included a sterile throat swab was then used to take the sample of pus discharge from the conjunctival sac and sent to lab for culture and sensitivity in a safe manner.Result: A total of 129 samples were taken from 105 patients, with 60 being females (57.14%) and 45 being males (42.50%). Sixty-four samples (49.60%) were taken from the right eye and 65 samples (51.40%) were taken from left eye. Twenty-four samples (18.60%) showed no growth after 48 hours of incubation under 37° C. Thirty-nine (30.20%) showed growth of Staphylococcus Epidermidis. Ampicillin showed resistance in most of the isolates 51.00% resistance while ceftriaxone 69.52 %, ciprofloxacin 65.00%, co-trimoxazole 84.76% and meropenem showed 93.33% sensitivity.Conclusion: Staphylococcus Epidermidis is the most common organism causing conjunctivitis is patients with nasolacrimal duct ...